2003
DOI: 10.1242/jcs.00231
|View full text |Cite
|
Sign up to set email alerts
|

α5β1 integrin mediates strong tissue cohesion

Abstract: Integrins and cadherins are considered to have distinct and opposing functions. Integrins are traditionally cited for their role in cell-substratum interactions, whereas cadherins are thought to mediate strong intercellular cohesion. Together, these adhesion systems play crucial roles in a wide variety of cellular and developmental processes including cell migration, morphology, differentiation and proliferation. In this manuscript we present evidence that integrins possess the ability to mediate strong interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
137
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 40 publications
8
137
0
Order By: Relevance
“…Here we used aggregates of N-cadherin transfected CHO cells, whose liquidity has been established earlier (49). It is quite likely that when structure formation is induced by the methods described here, aggregates of other cell types (in particular stem cells) will behave similarly to embryonic tissues, as far as their liquidity and ability to fuse is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Here we used aggregates of N-cadherin transfected CHO cells, whose liquidity has been established earlier (49). It is quite likely that when structure formation is induced by the methods described here, aggregates of other cell types (in particular stem cells) will behave similarly to embryonic tissues, as far as their liquidity and ability to fuse is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropic effects include cell proliferation, motility, differentiation, and survival, as shown in the collagen invasion assay (23) where cells are observed to form branched structures and invade a threedimensional collagen gel. Strong cell-cell and cell-matrix adhesion forces generated by cell adhesion molecules such as E-cadherins and integrins can attenuate such potentially invasive morphologies (24).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that TST can be used to predict and control the spatial relationship between different embryonic tissues 16,17 and also between genetically engineered cells, 18 can strongly influence the ability of tissues to interact with biomaterials, 19 correlates with invasive potential of lung tumors, 20 fibrosarcomas 21 and prostate cancers 22 and can be altered not only through direct manipulation of cadherin-based intercellular cohesion 18 -20 but also by manipulation of key extracellular matrix (ECM) molecules such as fibronectin (FN). 23,24 Any strategy aimed at increasing intercellular cohesive energy between tumor cells may be useful in restraining cells from detaching from the tumor mass. Dexamethasone (Dex) is a synthetic glucocorticoid that has broad uses in oncology.…”
mentioning
confidence: 99%